2018
DOI: 10.1038/s41368-018-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

ERK phosphorylation functions in invadopodia formation in tongue cancer cells in a novel silicate fibre-based 3D cell culture system

Abstract: To screen for additional treatment targets against tongue cancer, we evaluated the contributions of extracellular signal-related kinase (ERK), AKT and ezrin in cancer development. Immunohistochemical staining showed that ERK and ezrin expressions were significantly higher in invasive squamous cell carcinoma than in carcinoma in situ. To investigate the roles of ERK and ezrin in cancer development, we used the non-woven silica fibre sheet CellbedTM with a structure resembling the loose connective tissue morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
(27 reference statements)
3
25
0
Order By: Relevance
“…We evaluated the invasion depth of cancer cells in the vertical section of Cellbed, the results of which are shown in Figure 6. We had reported previously that cell projec- tions within HSC-3 and HSC-4 cells cultured in a Cellbed could be readily detected, in contrast to the results found using cells cultured in a 2D condition [8]. These cytological changes were also observed in this study, and we further show that HSC-3 and HSC-4 cells display similar cytological and histological characteristics regardless of the type of collagen (Fig.…”
Section: Collagen IV Coating Increases Invasion Depthsupporting
confidence: 67%
See 3 more Smart Citations
“…We evaluated the invasion depth of cancer cells in the vertical section of Cellbed, the results of which are shown in Figure 6. We had reported previously that cell projec- tions within HSC-3 and HSC-4 cells cultured in a Cellbed could be readily detected, in contrast to the results found using cells cultured in a 2D condition [8]. These cytological changes were also observed in this study, and we further show that HSC-3 and HSC-4 cells display similar cytological and histological characteristics regardless of the type of collagen (Fig.…”
Section: Collagen IV Coating Increases Invasion Depthsupporting
confidence: 67%
“…Pathobiology 2020;87:291-301 DOI: 10.1159/000509133 the term "tissueoid cell culture system" to refer to our 3D cell culture system. The tissueoid cell culture system has several advantages over other 3D cell culture approaches, such as Matrigel coating and spheroid cultures for the following reasons [21,22]: (1) The procedures undertaken for the culture system are very simple; (2) as the scaffold resists heat and organic solvents such as xylene or alcohol, cultured cells can be directly used for various types of staining; (3) pure cultured cells can be used for various experiments [8]; and (4) we can coat ECM on the silicate fibers of Cellbed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibition of ERK signaling inhibits tumor growth in various types of cancer, including gastric cancer (Wu et al, 2013), renal cell carcinoma (Fang et al, 2013), and rhabdomyosarcoma (Renshaw et al, 2013). We have also revealed that the activation of ERK in tongue cancer cell lines cultured three-dimensionally using silica fiber is associated with the formation of invadopodia (Noi et al, 2018).…”
Section: Discussionmentioning
confidence: 79%